2022
DOI: 10.3390/medicina58060792
|View full text |Cite
|
Sign up to set email alerts
|

The Use of near Infra-Red Radiation Imaging after Injection of Indocyanine Green (NIR–ICG) during Laparoscopic Treatment of Benign Gynecologic Conditions: Towards Minimalized Surgery. A Systematic Review of Literature

Abstract: Background and Objectives: To assess the use of near infrared radiation imaging after injection of indocyanine green (NIR–ICG) during laparoscopic treatment of benign gynecologic conditions. Materials and Methods: A systematic review of the literature was performed searching 7 electronic databases from their inception to March 2022 for all studies which assessed the use of NIR–ICG during laparoscopic treatment of benign gynecological conditions. Results: 16 studies (1 randomized within subject clinical trial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Indocyanine green (ICG) angiography is used across various medical fields for evaluation of tissue perfusion [ 24 ]. In gynecology [ 25 ], ICG is applied for visualization of the vascular perfusion of the vaginal cuff after total hysterectomy [ 26 , 27 ], of the ureteral course [ 28 ], and of endometriosis [ 29 , 30 ], as well as for detection of the sentinel lymph node [ 31 , 32 , 33 ]. The visualization of vascular perfusion of the vaginal cuff using ICG is feasible and complication-free but with unclear clinical profit, while a more objective analysis of its fluorescence has been established in colorectal surgery by applying the correlation between fluorescence and leakage of the colorectal anastomosis to determine further surgical steps [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indocyanine green (ICG) angiography is used across various medical fields for evaluation of tissue perfusion [ 24 ]. In gynecology [ 25 ], ICG is applied for visualization of the vascular perfusion of the vaginal cuff after total hysterectomy [ 26 , 27 ], of the ureteral course [ 28 ], and of endometriosis [ 29 , 30 ], as well as for detection of the sentinel lymph node [ 31 , 32 , 33 ]. The visualization of vascular perfusion of the vaginal cuff using ICG is feasible and complication-free but with unclear clinical profit, while a more objective analysis of its fluorescence has been established in colorectal surgery by applying the correlation between fluorescence and leakage of the colorectal anastomosis to determine further surgical steps [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in technology and minimally invasive surgical methods have drastically improved patient outcomes and decreased morbidity following gynecologic surgery [1, 2]. However, following a laparoscopic approach, it is often challenging to perform an early screening for complications that could lead to a secondary surgical look-up [3].…”
Section: Introductionmentioning
confidence: 99%
“…Still later, fluorescence guided surgery has been progressively studied and applied to robotic or laparoscopic gynecologic surgery, such as sentinel lymph node biopsy in gynecologic malignancies, endometriosis mapping, and vascular perfusion of the ureters, vagina, or ovaries [ 8 , 9 , 10 , 11 ] Systemically administered ICG is secreted initially through the liver, bile duct, and intestines, not the kidneys, and so, it has to be administered in retrograde instillation by ureteral catheter for intraoperative ureter visualization [ 12 ]. Recently, the illuminative identification of ureters through intraureteral ICG instillation and near-infrared fluorescence (NIRF) imaging has been reported to be useful during robotic or laparoscopic surgery [ 7 , 13 , 14 , 15 ]. Cabanes et al reported that this technique was applied to facilitate intraoperative ureteral dissection and accurately identify the ureteral pathway in real time in sixteen patients during gynecological oncology surgery; the surgeons could visualize both ureters and avoid ureteral injury in all patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%